POLITICAL DYNASTIES AND BUREAUCRATIC POLITICIZATION: A COMPARATIVE STUDY OF INDONESIA AND THE PHILIPPINES - Muslih Rodli, Ahmad (International Journal of Multidisciplinary Reseach, 2026)
This article analyzes the persistence of bureaucratic patronage in the context of decentralized democracies through a comparative study of Indonesia and the Philippines. Although democratization and merit-based reform are normatively expected to strengthen bureaucratic professionalism, empirical evidence demonstrates that these processes have instead opened opportunities for the consolidation of political dynasty power at the local level. By integrating the framework of neo-patrimonialism and principal-agent theory, this research argues that the primary problem lies in the structural distortion of delegation relationships: bureaucrats formally act as agents of the state and the public, but in practice function as de facto agents of political dynasties that control local executive authority. This study employs a qualitative comparative approach based on secondary data, policy documents, and previous empirical studies to identify key mechanisms of bureaucratic co-optation, including manipulation of recruitment and promotion, post-election mass transfers, and exploitation of legal loopholes in the merit system. Despite differences in institutional design particularly the constitutional position of the Civil Service Commission in the Philippines compared to the State Civil Apparatus Commission in Indonesia both countries exhibit similar patterns of bureaucratic neutrality erosion. To explain this convergence, this article proposes the Archipelagic Patronage Model, which emphasizes the interaction between geographical fragmentation, decentralization, weak horizontal accountability, and the informalization of formal rules in reinforcing political dynasty dominance over local bureaucracy.